Survival in patients with congenital heart disease and down syndrome. (3rd October 2022) - Engsner, S; Giang, K W; Dellborg, M; Fedchenko, M; Eriksson, P; Mandalenakis, Z
Abstract: Background: Increasing survivorship among patients with congenital heart disease (CHD) has been reported during the past decades. However, a number of patients with CHD have an associated Down syndrome diagnosis and the long-term prognosis is still debated. Purpose: The aim of the present study was to estimate the mortality risk in CHD patients with Down syndrome compared to a matched control population without CHD. Methods: We linked data from the Swedish National Patient Register and Cause of Death Register to identify all CHD patients born between January 1970 and December 2017. Then we identified all CHD patients with Down syndrome. Each CHD patient with Down syndrome was matched for sex and birth year with eight controls without CHD or Down syndrome from the Total Population Register. A Cox proportional regression model was used to estimate the mortality risk and Kaplan Meier for survival analysis. Results: In total, 3, 285 patients with CHD and Down syndrome and 26, 128 matched controls were identified. During a mean follow-up of 16.0 (±12.6) years, 558 CHD patients (17%) with Down syndrome, and 198 controls (0.76%) died. CHD patients with Down syndrome had 25.1 times higher risk of mortality (Hazard ratio 25.1, 95%, confidence interval (CI) 21.3–29.5) compared with controls. Patients with the most complex CHD were found to have the highest mortality risk (Hazard ratio 32.3, 95% CI 26.1–39.9). A decrease in risk of mortality during the first year of life was found between the two birth periods, risk of mortality was 46.8 (CI 29.5–74.0) in 1970–1989 and 17.7 (CI 12.8–24.42) 1990–2017. In addition, the mortality risk was two times (95% CI 1.94–2.31) higher for CHD patients with Down syndrome when compared to CHD patients without Down syndrome. Conclusion: The risk of mortality among CHD patients with Down syndrome was 25 times higher compared to controls without CHD or Down syndrome. The highest risk of mortality was found in patients with complex CHD. The survivorship rate was exponentially increased in CHD patients with Down syndrome that were born after 1990, determining the modern era of congenital heart care. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish state under an agreement between the Swedish Government and county Councils (ALF)